Influence analysis of time delay to active mass damper control system using pole assignment method. (1st December 2016) - Teng, J.; Xing, H.B.; Lu, W.; Li, Z.H.; Chen, C.J.
Abstract: To reduce the influence of time delay on the Active Mass Damper (AMD) control systems, influence analysis of time delay on system poles and stability is applied in the paper. A formula of the maximum time delay for ensuring system stability is established, by which the influence analysis of control gains on system stability is further arisen. In addition, the compensation controller is designed based on the given analysis results and pole assignment. A numerical example and an experiment are illustrated to verify that the performance of time-delay system. The result is consistent to that of the long-time delay control system, as well as to proof the better effectiveness of the new method proposed in this article. Highlights: Compensation controller is designed to eliminate time delay completely or partly. The relationship of system poles and time delay is deduced for controller design. Steel frame structure and its controller are built to verify the proposed method.